Pengaruh Konsumsi Konten TikTok terhadap Persepsi Mahasiswa dalam Seleksi Pasangan Hidup: (Studi Kasus di Universitas Muhamadiyah Ponorogo) - Usamah Al Mahdi; Muhammad Yassir (Yayasan Cendekia Gagayunan Indonesia, 2025)
Marriage is a sacred event for Muslims and marks the beginning of a new life with a chosen partner, making it crucial to consider key factors in selecting a spouse. This study, conducted at Universitas Muhammadiyah Ponorogo, aims to examine the influence of TikTok content on students' perceptions in choosing a life partner. Using a qualitative approach, data were collected through interviews with seven informants and analyzed descriptively with a case-study method. The findings reveal that TikTok content significantly shapes students' perspectives, particularly content related to lifestyle, romantic relationships, and beauty standards. This study highlights the substantial role of social media in influencing young generations' views on partner selection. The research contributes to understanding digital-era social dynamics, especially in higher education contexts.